Character Types of Millennial Children in High School - Novialdi, Novialdi; Noviyanti, Noviyanti; Husna, Zakhrifa (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2024)
This study examines the various character types of millennials currently found in high schools. Millennials, born between the early 1980s and the mid-1990s and early 2000s, are known for their unique characteristics influenced by technological advancements and social change. This study identified several dominant character types among millennial high school students, namely: Digital Natives: Students who are highly skilled in technology and social media, tend to be constantly connected to the virtual world, and have strong multitasking skills. Socially Sensitive: Students who show a strong concern for social and environmental issues, are active in social and community activities, and are often involved in campaigns or non-profit organizations. Ambitious and Competitive: Students who have clear academic and career goals, are highly achievement-oriented, and are frequently involved in various extracurricular activities to enhance their skills and experience. Creative and Innovative: Students who have a strong interest in art, design, or creative technology, often generate new ideas and engage in creative projects both inside and outside of school. This study also explores how these characteristics affect students' social interactions, academic achievement, and emotional well-being1 Quantitative research is a type of research that produces findings that can be achieved (obtained) through the use of statistical procedures or other forms of quantification. The informants of this study were 65 people. The results of this study show that Islamic Religious Education has a positive and significant influence on the character of students. This can be proven from the results of the Islamic Religious Education hypothesis test which shows a t-value of 6.171 > 2.000 or positive with a significance level of 0.000 < 0.05. This means that the hypothesis in this study rejects Ho and accepts Ha. And obtained the linear regression value Y = 14.688 + 0.661X, sig. Level 0.000 < 0.05 (alpha value), based on the output obtained of 0.661, meaning that if Islamic Religious Education is better then the character will experience an increase of 66.1%. The influence of Islamic Religious Education on the character of students based on the results of the determination coefficient analysis obtained R2 (R Square) of 0.377 (0.614 x 0.614) or 37.7%. This problem shows that the independent variable (Islamic Religious Education) used is able to explain 37.7% of the dependent variable (character). While 62.7% is influenced or explained by other variables not included in this study.